First fossil Eriocottidae discovered in Eocene Baltic amber (Insecta: Lepidoptera) - Ngô-Muller, Valerie; Engel, Michael S.; Nel, Andre; Nel, Jacques (Zootaxa, 2020)
Eocompsoctena macroptera gen. et sp. nov., the first fossil eriocottid moth, is described from Baltic amber and attributed to the Compsocteninae. Comparisons are provided with the related families Dryadaulidae, Meessiidae, Psychidae, and Tineidae. The new species confirms the antiquity of ‘Tineoidea’ grade diversification. The putative Gondwanan origin of Eriocottidae is discussed.